Crossing Boundaries in a Collaborative Modeling Workspace. Issue 9 (2nd September 2017) - Morisette, Jeffrey T.; Cravens, Amanda E.; Miller, Brian W.; Talbert, Marian; Talbert, Colin; Jarnevich, Catherine; Fink, Michelle; Decker, Karin; Odell, Eric A.
ABSTRACT: There is substantial literature on the importance of bridging across disciplinary and science–management boundaries. One of the ways commonly suggested to cross boundaries is for participants from both sides of the boundary to jointly produce information (i.e., knowledge co-production). But simply providing tools or bringing people together in the same room is not sufficient. Here we present a case study documenting the mechanisms by which managers and scientists collaborated to incorporate climate change projections into Colorado's State Wildlife Action Plan. A critical component of the project was the use of a collaborative modeling and visualization workspace: the U.S. Geological Survey's Resource for Advanced Modeling (RAM). Using video analysis and pre/post surveys from this case study, we examine how the RAM facilitated cognitive and social processes that co-produced a more salient and credible end product. This case provides practical suggestions to scientists and practitioners who want to implement actionable science.